Opportunities for reinforcing cross-border railway connections: the case of the Liège (Belgium) – Maastricht (the Netherlands) connection. Issue 1 (2nd January 2020) - Christmann, Nathalie; Mostert, Martine; Wilmotte, Pierre-François; Lambotte, Jean-Marc; Cools, Mario
ABSTRACT: Efficient mobility is an essential driving force for the development of cross-border (CB) regions. The different settings and visions of neighbouring CB entities may lead to unsatisfactory transport connections across the border. This case study of a CB connection focuses on this issue and highlights, by means of a comparative analysis, how the differences in six perspectives (the economic context; urban and regional planning in Belgium and the Netherlands; the structure of the rail network; barriers in the exploitation of the railway; the current travel demand by rail; and the governance, public planning and policy context) lead to an unsatisfactory rail connection between Liège (Belgium) and Maastricht (the Netherlands). Based on the results of the analysis, we suggest reinforcing cross-mobility connections through several tools such as (i) the development of a common governance, not only at the institutional level but also at the counter level of institutional level, by including economic and social stakeholders; (ii) the development of joint technical projects in relation to the infrastructure, communication systems and the rolling stock; and (iii) the strengthening of flows between the two sides of the border, especially the home-work flows.